Genetic divergence in mitochondrial DNA of Anopheles nuneztovari (Diptera: Culicidae) from Brazil and Colombia - Scarpassa, Vera Margarete (2000)
In the present study, we have examined the variability in Anopheles nuneztovari mitochondrial DNA of three populations from the Brazilian Amazon and one from western Colombia (Sitronela), using four restriction endonucleases (BclI, ClaI, HindIII, SstI). The haplotype diversity (h) was slightly elevated in all populations (0.5000 to 0.6765), whereas the nucleotide diversity (π) was lower in the Sitronela population (0.0029) and higher in populations from the Brazilian Amazon (0.0056 to 0.0098). The degree of sequence divergence (δ) estimated within the Brazilian Amazon and that in Sitronela (0.0329 to 0.0371) suggests that these geographic populations of A. nuneztovari may eventually constitute separate species. The low sequence divergence values among the three Brazilian Amazon populations (0.0012 to 0.0031) indicate that these populations are genetically similar. These results are consistent with those recently reported for allozymes of these same populations.